2011
DOI: 10.1002/hed.21489
|View full text |Cite
|
Sign up to set email alerts
|

Stent migration to the ileum—A potentially lethal complication after montgomery salivary bypass tube placement for hypopharyngeal stenosis after laryngectomy

Abstract: To avoid potentially lethal complications associated with MSBT migration into the intestinal tract, we recommend secure fixation of the MSBT to a nasogastric tube.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…Our inclusion criteria for stent placement included: laryngectomy extending to the base of the tongue, hypopharynx, cervical oesophagus or cervical skin; and/or primary radiochemotherapy. 13 We found that the transparent model was better in the case of free flap reconstruction because it enabled flap survival to be monitored endoscopically. The main indications for this stent are: pharyngocutaneous fistula after total laryngectomy; cervical oesophageal stenosis; and tracheoesophageal fistula.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Our inclusion criteria for stent placement included: laryngectomy extending to the base of the tongue, hypopharynx, cervical oesophagus or cervical skin; and/or primary radiochemotherapy. 13 We found that the transparent model was better in the case of free flap reconstruction because it enabled flap survival to be monitored endoscopically. The main indications for this stent are: pharyngocutaneous fistula after total laryngectomy; cervical oesophageal stenosis; and tracheoesophageal fistula.…”
Section: Discussionmentioning
confidence: 92%
“…, 12 There are two models available – transparent or radiopaque – with a diameter ranging between 8 and 20 mm. We preferred to use the radiopaque model with a diameter of 16–20 mm (larger diameter), as this model: (1) gives good protection of the neopharynx from saliva; (2) prevents stenotic scarring of the neopharynx (often the cause of fistula development); and (3) can be detected radiologically in the case of intestinal migration 13 . We found that the transparent model was better in the case of free flap reconstruction because it enabled flap survival to be monitored endoscopically.…”
Section: Discussionmentioning
confidence: 99%
“…One arterioesophageal fistula occurred following laryngectomy due to a retroesophageal subclavian artery 21 . A distal migration of salivary bypass tube caused intestinal perforation following laryngectomy 22 . An aortoesophageal fistula occurred in a paediatric patient following the long-term use of a salivary bypass tube to reconstruct oesophageal atresia 23 …”
Section: Resultsmentioning
confidence: 99%
“…Serious complications from pharyngeal SBT are rare but have been described as a direct result of their use. One patient developed peritonitis and went on to die following migration of the tube into the ileum [47] and arterio-esophageal fistulas have been described, one of which was fatal [48, 49]. However, they are generally safe with only mild complications such as discomfort and granulation tissue formation [43].…”
Section: Discussionmentioning
confidence: 99%